Frantic Panoramas : American Literature and Mass Culture, 187-192 - Bentley, Nancy, 1961- (Book collections on Project MUSE., 2009)
Late nineteenth-century America saw an explosion in mass culture-from sensationalist tabloid newspapers to amusement parks to Wild West shows. Historians and critics have traditionally observed the advent of mass culture as undermining literature's central role in the public sphere. Literary writers of the time either reacted with a public show of disdain or retreated to conduct their own private experiments in style and form. In Frantic Panoramas, Nancy Bentley questions these narratives of opposition.For literary writers, Bentley explains, the confrontation with mass culture was less a retreat than a transformation, an ordeal through which habits of contemplative appreciation could be refashioned into new forms of critical thought. By grappling with the energies that marked mass culture, authors came to recognize kinds of human experience that were only then becoming visible as public. William Dean Howells shaped the plots of his novels around tabloid events like rail and trolley accidents and the public chaos of apartment house fires. Although Henry James was distressed at the way dime fiction had changed the very definition of literature, his meditations on mass culture led him to reimagine the novel as a collective "workshop" in which authors and readers jointly discovered new meaning. Bentley offers close readings of these and other writers such as Edith Wharton, James Weldon Johnson, Pauline Hopkins, and Gertrude Bonnin to demonstrate how leading artists took inspiration from commercial culture to create new and distinct literary forms.Drawing on original archival research and a historically grounded theory of realism, Frantic Panoramas is an innovative and comprehensive study of how the emergence of mass culture affected literary culture in America.